2016
DOI: 10.1007/s10286-016-0375-5
|View full text |Cite
|
Sign up to set email alerts
|

Heart rate variability during sleep in children with autism spectrum disorder

Abstract: Purpose Autonomic dysfunction has been reported in autism spectrum disorder (ASD). Less is known about autonomic function during sleep in ASD. The objective of this study is to provide insight into the autonomic cardiovascular control during different sleep stages in ASD. We hypothesized that patients with ASD have lower vagal and higher sympathetic modulation with elevated heart rate (HR), as compared to typical developing children (TD). Methods We studied 21 children with ASD and 23 TD children during over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
42
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 53 publications
(44 citation statements)
references
References 37 publications
2
42
0
Order By: Relevance
“…Furthermore, the outcome of the mixed model analysis supports that this phenomenon in HRV is independent of age in children and adolescents aged 3-13 years. Similar to results in adults (29) and children (30), we showed that the most significant drop in heart rate (increase in mean NN) occurs between sleep onset and SWS1 and continues to drop only in SWS cycles as time asleep progresses. Unlike Baharav et al who in 10 children and adolescents showed no difference in heart rate between sleep stages (31), we showed that heart rate (mean NN) was significantly different between some SWS periods and REM sleep periods across the night but that all sleep stage cycles were not the same in uninterrupted sleep.…”
Section: Discussionsupporting
confidence: 87%
“…Furthermore, the outcome of the mixed model analysis supports that this phenomenon in HRV is independent of age in children and adolescents aged 3-13 years. Similar to results in adults (29) and children (30), we showed that the most significant drop in heart rate (increase in mean NN) occurs between sleep onset and SWS1 and continues to drop only in SWS cycles as time asleep progresses. Unlike Baharav et al who in 10 children and adolescents showed no difference in heart rate between sleep stages (31), we showed that heart rate (mean NN) was significantly different between some SWS periods and REM sleep periods across the night but that all sleep stage cycles were not the same in uninterrupted sleep.…”
Section: Discussionsupporting
confidence: 87%
“…Only artefact-free recording time (AFRT) was included in the analysis. Acceptable recordings contained at least 4 hours of data including a period of presumed REM as determined by increased heart rate variability 13. If insufficient data were obtained, a repeat recording was undertaken with the family’s agreement.…”
Section: Methodsmentioning
confidence: 99%
“…For obvious reasons, routinely used techniques in the autonomic laboratory, such as the tilt-table test, cold pressor test or Valsalva maneuver, cannot be used while patients are sleeping. Some investigators are able to perform microneurography recordings or make catecholamine measurements on their subjects during sleep, but because virtually every polysomnography includes electrocardiography, heart rate variability has become the gold standard to study the autonomic nervous system during sleep, notwithstanding its limitations [8,17]. In this issue, Bugalho and colleagues [4] report their measurements of heart rate variability during sleep in patients with RBD; their results appear to show that these patients have reduced vagal modulation compared to patients without RBD.…”
mentioning
confidence: 99%